KVPY #1

Find the sum of all positive integers n n for which 1 3 + 2 3 + + ( 2 n ) 3 1 2 + 2 2 + + n 2 \dfrac{1^3 + 2^3 + \cdots + (2n)^3 }{1^2 + 2^2 + \cdots + n^2} is also an integer.

For more KVPY questions, try my set .


The answer is 8.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Md Zuhair
Mar 24, 2017

It should be

6 n ( 2 n + 1 ) n + 1 = 6 n ( n + 1 ) + 6 n 2 n + 1 = 6 n + 6 n 2 n + 1 \dfrac{6n(2n+1)}{n+1} = \dfrac{6n(n+1) + 6n^2}{n+1} = 6n + \dfrac{6n^2}{n+1}

Tapas Mazumdar - 4 years, 2 months ago

N = 1 3 + 2 3 + 3 3 + + ( 2 n ) 3 1 2 + 2 2 + 3 2 + + n 2 = ( 2 n ( 2 n + 1 ) 2 ) 2 n ( n + 1 ) ( 2 n + 1 ) 6 = 6 n 2 ( 2 n + 1 ) 2 n ( n + 1 ) ( 2 n + 1 ) = 6 n ( 2 n + 1 ) n + 1 = 6 n ( 2 n + 2 ) 6 n n + 1 = 12 n ( n + 1 ) 6 ( n + 1 ) + 6 n + 1 = 12 n 6 + 6 n + 1 \begin{aligned} N & = \frac {1^3+2^3+3^3+\cdots + (2n)^3}{1^2+2^2+3^2+\cdots + n^2} \\ & = \frac {\left(\frac {2n(2n+1)}2 \right)^2}{\frac {n(n+1)(2n+1)}6} \\ & = \frac {6n^2(2n+1)^2}{n(n+1)(2n+1)} \\ & = \frac {6n(2n+1)}{n+1} \\ & = \frac {6n(2n+2)-6n}{n+1}\\ & = \frac {12n(n+1)-6(n+1)+6}{n+1} \\ & = 12n - 6 + \frac 6{n+1} \end{aligned}

For N N to be an integer, 6 n + 1 \dfrac 6{n+1} has to be an integer and there are only three cases of positive integer n = 1 , 2 , 5 n=1, 2, 5 . And, their sum is 1 + 2 + 5 = 8 1+2+5= \boxed{8} .

I don't think 1 3 + 2 3 + 3 3 + . . . . . + ( 2 n ) 3 1^3+2^3+3^3+.....+(2n)^3 can be written as ( 2 n ( 2 n + 1 ) 2 ) 2 (\dfrac{2n(2n+1)}{2})^2 since 2 n 2n is not the general term of the series. Unless and until we don't have the n t h n^{th} term, we can't use that formula.

Skanda Prasad - 3 years, 9 months ago

Log in to reply

Let m = 2 n m=2n , then 1 3 + 2 3 + 3 3 + + m 3 = ( m ( m + 1 ) 2 ) 2 1^3+2^3+3^3 + \cdots + m^3 = \left(\dfrac {m(m+1)}2\right)^2 . Replace m m with 2 n 2n .

Chew-Seong Cheong - 3 years, 9 months ago

Did the same way.

Niranjan Khanderia - 3 years, 8 months ago
Topper Forever
Mar 30, 2017

After solving the complex above we get

12n^2+6n/n+1

6n(n+1)+6n^2/n+1

(6n)+(6n^2)/n+1

(6n(n+1)-6n)/n+1

6n/n+1

(6(n+1)-6)/6

6/n+1

n=1,2,5

N=1+2+5=8

Tapas Mazumdar
Mar 30, 2017

1 3 + 2 3 + + ( 2 n ) 3 1 2 + 2 2 + + n 2 = k = 1 2 n k 3 k = 1 n k 2 = ( 2 n ) 2 ( 2 n + 1 ) 2 4 n ( n + 1 ) ( 2 n + 1 ) 6 = 6 n ( 2 n + 1 ) n + 1 \dfrac{1^3 + 2^3 + \cdots + (2n)^3 }{1^2 + 2^2 + \cdots + n^2} = \dfrac{\sum_{k=1}^{2n} k^3}{\sum_{k=1}^{n} k^2} = \dfrac{\frac{{(2n)}^2 {(2n+1)}^2}{4} }{\frac{n (n+1) (2n+1)}{6}} = \dfrac{6n(2n+1)}{n+1}

Now for 6 n ( 2 n + 1 ) n + 1 Z + \dfrac{6n(2n+1)}{n+1} \in \mathbb{Z}^{+} , three situations are possible

( I ) n + 1 6 n { 1 , 2 , 5 } \mathbf{(I)} \ n+1 \ | \ 6 \implies n \in \{1,2,5\}

( I I ) n + 1 n n \mathbf{(II)} \ n+1 \ | \ n \implies n \in \emptyset

( I I I ) n + 1 2 n + 1 n + 1 n + ( n + 1 ) n + 1 n n \mathbf{(III)} \ n+1 \ | \ 2n+1 \implies n+1 \ | \ n + (n+1) \implies n+1 \ | \ n \implies n \in \emptyset

Thus the sum of all values of n n is 1 + 2 + 5 = 8 1+2+5 = \boxed{8} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...